Analisis Validitas Modul Berbasis Augmented Reality dan Literasi Sains (ARLISA) pada Materi Energi Terbarukan - Rizqillah, Inanda Aulia; Kholiq, Abd. (IPF: Inovasi Pendidikan Fisika, 2023)
There have been many developments in module, but they are different from the ARLISA module. This is because the ARLISA module being developed is equipped with features that are able to train students' scientific literacy and augmented reality features so that learning feels more real, interesting and varied. This study focuses on analyzing the validity of the ARLISA module which has been developed using the ASSURE development research model (Analyze Learner, State Standards and Objectives, Select Strategies, Technology, Media, and Materials, Utilize Technology, Media, and Materials, Require Learner Participation, Evaluate and Revise). Module validation is carried out by three validators who are expert lecturers in the field of learning media. Module validity is viewed from four aspects, namely learning aspects, material aspects, language aspects, and media aspects. The results showed that the validity scores obtained for these four aspects were 96%, 96%, 97% and 97%. So that the percentage of the average score of the ARLISA module validation is 97% with a very valid category. So it can be stated that the ARLISA module is appropriate for use as a learning medium to train students' scientific literacy in learning physics on renewable energy material. Keywords: Module, Augmented Reality, Science Literacy, Renewable Energy